Making modelling count - increasing the contribution of shelf-seas community and ecosystem models to policy development and management. (November 2015) - Hyder, Kieran; Rossberg, Axel G.; Allen, J. Icarus; Austen, Melanie C.; Barciela, Rosa M.; Bannister, Hayley J.; Blackwell, Paul G.; Blanchard, Julia L.; Burrows, Michael T.; Defriez, Emma; Dorrington, Tarquin; Edwards, Karen P.; et al.
Abstract: Marine legislation is becoming more complex and marine ecosystem-based management is specified in national and regional legislative frameworks. Shelf-seas community and ecosystem models (hereafter termed ecosystem models) are central to the delivery of ecosystem-based management, but there is limited uptake and use of model products by decision makers in Europe and the UK in comparison with other countries. In this study, the challenges to the uptake and use of ecosystem models in support of marine environmental management are assessed using the UK capability as an example. The UK has a broad capability in marine ecosystem modelling, with at least 14 different models that support management, but few examples exist of ecosystem modelling that underpin policy or management decisions. To improve understanding of policy and management issues that can be addressed using ecosystem models, a workshop was convened that brought together advisors, assessors, biologists, social scientists, economists, modellers, statisticians, policy makers, and funders. Some policy requirements were identified that can be addressed without further model development including: attribution of environmental change to underlying drivers, integration of models and observations to develop more efficient monitoring programmes, assessment of indicator performance for different management goals, and the costs and benefit of legislation. Multi-model ensembles are being developed in cases where many models exist, but model structures are very diverse making a standardised approach of combining outputs a significant challenge, and there is a need for new methodologies for describing, analysing, and visualising uncertainties. A stronger link to social and economic systems is needed to increase the range of policy-related questions that can be addressed. It is also important to improve communication between policy and modelling communities so that there is a shared understanding of the strengths and limitations of ecosystem models. Highlights: Ecosystem models have great potential to support decision-making, but UK examples are limited. Ecosystem models would be more widely used with better awareness of capability, quality assurance, and uncertainty. UK ecosystem modelling with immediate value to policy and capability gaps are identified. Communities of policy makers and scientists are needed to co-develop ecosystem models.